REDESAIN SALURAN DRAINASE DI KELURAHAN WUNDUDOPI (Studi Kasus: Jl. D.I Panjaitan - Jl. Y. Wayong By Pass) - Nur Salam Saleng; Try Sugiyarto Soeparyanto; Fathur Rahman Rustan (PRODI D3 TEKNIK SIPIL, 2018)
Abstract Wundudopi Village is one of the villages in Baruga Subdistrict that has performance issues on drainage channels. With high rainfall intensity and poor drainage systems, especially in Baruga Subdistrict, various problems arise which can damage existing infrastructure. The purpose of this study is to redesign drainage channels in Wundudopi Village. In analyzing the performance of the drainage channel, an analysis of the capacity of the channel is carried out, the calculation done based on the planned discharge, then obtaining the plan channel dimensions and its capacity after that is compared with the existing channel carrying capacity based on the existing existing channel dimensions.Based on the results of the performance analysis of several channels that are not safe obtained from several channel segments viewed from the existing and planned channels because the planned runoff flow is greater than the existing runoff channel flow in the field and the absence of existing channels / dimensions at the study site. Abstrak Kelurahan Wundudopi merupakan salah satu Kelurahan di Kecamatan Baruga yang mempunyai persoalan kinerja saluran drainase dengan intensitas hujan yang tinggi serta sistem drainase yang kurang baik menyebabkan berbagai persoalan timbul yang nantinya dapat merusak infrastruktur yang sudah ada.Tujuan dari penelitian ini adalah untuk redesain saluran drainase di Kelurahan Wundudopi. dalam menganalisis kinerja saluran drainase dilakukan analisis kapasitas tampung saluran, perhitungan dilakukan berdasarkan debit rencana, kemudian didapatkan dimensi saluran rencana dan kapasitas tampungnya setelah itu dibandingkan dengan kapasitas tampung saluran eksisting berdasarkan dimensi saluran eksisting yang ada.Berdasarkan hasil analisis kinerja saluran beberapa saluran yang tidak aman diperoleh dari beberapa segmen saluran dilihat dari saluran rencana dan eksisting dikarenakan debit limpasan saluran yang direncanakan lebih besar dibandingkan debit limpasan saluran yang ada dilapangan serta tidak adanya saluran/dimensi eksisting pada lokasi penelitian.